EL RETABLO EN LA ESCUELA SEVILLANA DEL SEISCIENTOS - Dabrio González, María Teresa (Imafronte, 1989)
This paper makes a synthesis of those constants distinguishing the seventeenth-century Sevillian retable in each of its stages. We start with a historiographic survey in which the main contributions are pinted out, as well as the methodology followed by the dlfferent authors. The study deals maitily with forms, making the dominatit aestheiics and the evolution produced in every stylistic stage stand out. Through the main artists and examples of their professional rask, we arrest our attention on the features dejining the typological schemes used in a just not homogeneous century. The manierist heritage, the ways of Baroque. the aesthetics of both Alfotisos, the aesthetics of Rivas brothers, the contributions of Bernardo Simóti de Pineda and the epigones are the links articulating the development of this analysis.